The World Bank and the Land Center for Human Rights: spaces of contested meaning - Whitmire, Keith Glenn (AUC Knowledge Fountain, 2011)
Since the 1970s, the World Bank has been engaged in a project of neo-liberal economic reform and social change in the Egyptian countryside. These reforms have resulted in profound changes in the countryside, including loss of owned or rented land by smallholders due to impoverishment and social change. Though the effects of the World Bank's views have been seen in the countryside and in greater Egypt, the particular nature of these conceptions and how they affect policy remains obscure. Meanwhile, organizations such as the Land Center for Human Rights are conceptually and geographically closer to Egyptian farmers and provide a separate and distinct point of view that opposes the Bank. Therefore, the purpose of this project is to perform a discursive analysis of the views of the World Bank and the Land Center for Human Rights on land, education, and moral economy in Egypt in order to ascertain their effects on economic and social life in Egypt.